Analisis Perjanjian Kerja Waktu Tertentu Dan Perlindungan Hukum Pada PT. Telmark Integrasi Indonesia Dalam Perspektif UU No. 11 Tahun 2020 Tentang Cipta Kerja - Harita, Wisu vorizato; Mudiparwanto, Wahyu Adi (JATIJAJAR LAW REVIEW, 2023)
Many companies use a Specific Time Work Agreement (PKWT) system for their workers to streamline expenses. However, in practice, it is not uncommon to encounter violations that are not in accordance with Law No. 11 of 2020 on Job Creation. This study uses a normative-empirical method with data collection techniques in the form of literature studies that have been studied legally by secondary, tertiary, and analyzed by means of a qualitative approach. Based on the research results, the authors found a discrepancy between PT. Telmark Integration Indonesia in the implementation of PKWT in Article 81 number 14 and Article 81 number 15 on Law No. 11 of 2020 on Job Creation, namely a probationary period for workers. Furthermore, the authors found that PT. Telmark Integrasi Indonesia in providing legal protection has not all been implemented in accordance with the legislation Article 156 number 44 on Law No. 11 of 2020 on Job Creation in which the company only gives workers rights starting from the remaining working period of the worker. Legal remedies that can be taken by workers are holding deliberations or called bipartite up to reporting to relevant agencies according to what is regulated in Article 3 on Law No. 2 of 2004 on Settlement of Industrial Relations Disputes.